PENGARUH PEMBIAYAAN SYARIAH TERHADAP PERTUMBUHAN EKONOMI DI INDONESIA - Tullah, Syaaqilah; Oktaviana , Yunita; Zain, Ziken Muhammad; Putri, Widya Eka Andita; Catrunnada, Femmy (Jurnal Ekonomi & Bisnis, 2024)
Economic growth is one of the benchmarks of the success of economic development in a country, so it becomes a goal that every country wants to achieve. The financial sector plays an important role in driving a country's economic growth, acting as a driver of real sector growth. Thus, the presence of Islamic banking in the financial sector in Indonesia must be able to contribute to increasing the growth of the real sector. Therefore, this study aims to explore how Islamic financing affects economic growth, wealth distribution, financial stability, and its contribution to sustainable and inclusive economic development in Indonesia. This study used a qualitative approach with literature study and descriptive analysis. The results of this study indicate that sharia financing had a positive and significant effect on economic growth in Indonesia. Financing as one of the financial instruments of sharia banking has quite a large potential to contribute to the development of the real sector, especially in helping to overcome capital constraints faced in the MSMEs sector. Sharia financing is one of the most important alternative sources of financing for entrepreneurs to obtain business capital. Thus, the presence of Islamic banking in the financial sector in Indonesia has a major contribution in encouraging the growth of the real sector so that its existence is expected to encourage fair, prosperous and sustainable economic growth in accordance with the principles and values ??contained in Islamic law.